Soil microbial properties and apple tree performance under conventional and organic management - Meyer, André Harold (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
Conventional (CON) soil management that permits the use of agrochemicals is currently the most common form of management in Western Cape deciduous fruit orchards. There is increasing pressure to minimise or eliminate synthetic agrochemical usage due to its potentially harmful effect on the environment, particularly to non-target soil microorganisms, and to the functions and processes they perform or mediate. In apple orchards, organic (ORG) practices exclude the use of synthetic pesticides and herbicides making use instead of organic fertilisers and naturally derived products as defined by organic certification programs. ORG practices aim to improve nutrient availability, yield, and long-term orchard sustainability relative to CON orchard management practices. If ORG and CON orchard floor management practices affect orchard ecosystems differently, such differences should be measurable in terms of differences in microbiological parameters. In this thesis it is hypothesised that ORG practices would induce positive soil microbiological responses in Western Cape apple orchards relative to CON practices, and by inference general soil health and apple tree performance. To test this hypothesis a polyphasic approach was adopted. This involved measurement of soil microbial activities and functional diversities, by enzyme activity (using colorimetric assays) and carbon-substrate utilisation (using the BIOLOGâ„¢ system), respectively. With reference to the enzyme analyses, the performance of a literature-validated, enzyme-based soil health index was also tested. The analyses were supported by coarse-level comparisons of the magnitude of bacteria, fungi, actinobacteria and total heterotroph populations using traditional culturing techniques (dilution plating on growth media). The extent to which the microbial status differed between the applied ORG and CON treatments was thought likely to reflect such treatment-induced variables as soil nutrient status, apple tree nutritional response, tree growth and yield, all of which were determined. Because the root systems of deciduous fruit trees commonly extend to depths >60 cm in well-prepared soils, microbial enzyme activities in the soil depth intervals corresponding to the lower rootzone, were also investigated. This research was carried out in a randomized field trial. Finally, to gain a broader understanding of the effects of contrasting soil management systems on soil microbiology under a greater variety of environmental conditions, arbuscular mycorrhizal (AM) fungal dynamics were explored in a survey of commercial apple orchards. These orchards were selected to span the range of environmental conditions that occur in the apple production areas of the Western Cape. Orchard soils under ORG management promoted richer microbial ecosystems, and appeared to be better able to sustain community metabolic diversity and, by inference, the functions mediated by soil microbial communities, than those under CON management. This implies that ORG approaches possibly afford a better option to sustain critical ecosystem functions than CON management. This possibly explains why use of straw mulches and compost in accordance with ORG practices, compared with CON practices, promoted Î²-glucosidase, acid phosphatase and urease activities rather than affecting the abundance of the micro-organisms that produce these enzymes. Enzyme activities in the 0"“30 cm soil intervals were also more effectively promoted by ORG than CON practices, although no differences were observed at lower depth intervals. ORG practices promoted functional AM associations more effectively than CON practices, but the abundance of glomalin, a beneficial by-product of AM fungi, was unaffected. The greater enzyme activities and higher root colonisation levels in the ORG treatments probably contributed to improved nutritional effects that caused greater vegetative growth, but lower yields, in the ORG treatments. Yield suppression was conceivably due to excessive vegetative growth induced by oversupply of compost and the mineral nutrients contained therein. The survey of Western Cape apple orchards suggested that neither glomalin nor root colonisation bore any specific relationship to production area, cultivation practice, scion x rootstock combination, or, in the case of root colonisation, with any chemical parameters. However, the effect of season on glomalin was conclusively shown, being higher in summer than in spring, as was the lack of any effect of year on glomalin and root colonisation. Collectively, these results showed that ORG soil management promote soil microbiology, soil nutrient status, and apple tree performance compared to CON management.
Keywords: Soil management -- South Africa -- Western Cape; Agricultural chemicals -- Environmental aspects; Soil microbiology -- South Africa -- Western Cape; Vesicular-arbuscular mycorrhizas; Enzymes Biotechnology; Apples Organic farming -- South Africa -- Western Cape